BIOMETRICS OF MULUNGU SEEDS FROM DIFFERENT MOTHER PLANTS IN THE SEMI-ARID REGION OF PARAÍBA, BRAZIL - Bezerra, Ana Carolina (2022)
Erythrina velutina Willd. (Fabaceae) is drought tolerant and has the potential for reforestation in the semi-arid region. The response of its seeds to the environmental conditions of each production area influences their size, weight, physiological potential, and health. Thus, this study aimed to assess how the environmental conditions of the different regions of Paraíba influence the biometric characteristics of E. velutina seeds. Seeds from 19 mother plants collected in Juru, Sumé, Araçagi, Guarabira, São João do Cariri, Esperança, Queimadas, Cuité, Boa Vista, and Areia, in the state of Paraíba, Brazil, were used in this study. Water content, thousand-seed weight, and biometric characteristics (length, width, and thickness) were determined in the seeds from each location. The water content ranged from 3.11 to 6.84%, while the thousand-seed weight was higher in mother plants grown in Sumé and Cuité. Seed length ranged from 9.00 to 16.84 mm, being higher in mother plants grown in Juru. Seed thickness and width ranged from 5 to 12.99 mm and were larger in mother plants from Cuité. Temperature, humidity, solar radiation, wind, and precipitation caused variations in the length, width, and thickness of E. velutina seeds, with higher means observed in mother plants grown in Cuité.